Detection of mycotoxins in opaque beer production - Marume P.; Ndlovu N; Manhokwe S; Ndlovu C. (African Journal of Biological Sciences, 2023)
In Zimbabwe opaque beer is one of the most common alcoholic beverages. This study was aimed at detecting aflatoxins and Ochratoxin A (OTA) in commercial opaque beer brewing. Aflatoxins and OTA are mycotoxins produced by fungi. Maize, sorghum malt and opaque beer samples were used for microbiological plating and multi mycotoxin extraction. Aflatoxins, OTA, Aspergillus spp, total viable count, coliforms, Lactobacillus spp, Salmonella, Shigella, Staphylococcus aureus were assessed. Mycotoxins were separated using an High Performance Liquid Chromatography (HPLC). Aflatoxins were not detected in all the samples. OTA concentration for malt was 18 μg/kg, 5.2 μg/kg in beer and absent in maize. Fungi identified in maize were Aspergillus flavus, Aspergillus niger, Aspergillus carbonarius, and Aspergillus fumigatus. Malt contained Aspergillus flavus and Aspergillus carbonarius. Fungi observed in beer were Aspergillus flavus and Aspergillus niger. The beer may need heat treatment methods in order to remove the microorganisms identified and prolong shelf life of the product.